MAKING PERFORMANCE-BASED BUDGETING WORKS IN SOME LOCAL GOVERNMENTS OF INDONESIA - Dyah Mutiarin, Achmad Nurmandi (International Public Organization Association, 2013)
After the political reform in 1998, Government of Indonesia have implemented performance-based budgeting. This schema requires the existence of strategic plan and its clear indicators of each program. This paper try to investigate the implementation of performance based budgeting in some local governments. Performance indicators used are input, output, outcome, benefit and impact. Comparative study of local government of Indonesia pointed out that implementation of a performance-based budgeting facing constraints both internal and external factor, namely the limitation of funds, limited human resources, weak support of legislative institutions and the limitations performance data. From the results of this study the author can recommend that theoretically the implementation performance management in government organization of developing countries requiring internal support organizations and political support from the local council. Practically, although Indonesia already has a complete performance-based budget regulation, but local implementation of budget policy on the ground are facing locally factor constraints.